2008
DOI: 10.1007/s12194-008-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CT screening for lung cancer with automatic exposure control: phantom study

Abstract: We conducted a study to determine optimal scan conditions for automatic exposure control (AEC) in computed tomography (CT) of low-dose chest screening in order to provide consistent image quality without increasing the collective dose. Using a chest CT phantom, we set CT-AEC scan conditions with a dose-reduction wedge (DR-Wedge) to the same radiation dose as those for low-tube current, fixed-scan conditions. Image quality was evaluated with the use of the standard deviation of the CT number, contrast-noise rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Study findings have shown greater variability and inaccuracy in volume determination of small nodules compared with large nodules with different slice thicknesses. [38][39][40] Winer-Muram and colleagues 41 found that an increase in slice thickness leads to an increase in overestimation of nodule volume. Our data indicates that MBIR (IMR) improves the image quality of LDCT more than hybrid algorithm (iDose) which is in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Study findings have shown greater variability and inaccuracy in volume determination of small nodules compared with large nodules with different slice thicknesses. [38][39][40] Winer-Muram and colleagues 41 found that an increase in slice thickness leads to an increase in overestimation of nodule volume. Our data indicates that MBIR (IMR) improves the image quality of LDCT more than hybrid algorithm (iDose) which is in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The anthropomorphic chest phantom (LSCT001; Kyoto Kagaku Co., Kyoto, Japan) 12 , 15 , 16 , 17 used in this study has a chest circumference of 930 mm and a height of 370 mm, modeling Japanese adult men of 40 years of age or older. The materials used in the phantom are a radiographic water‐equivalent substance for the chest wall and mediastinum and a radiographic bone‐equivalent substance for the vertebrae and ribs.…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, the effect of acquisition and reconstruction parameters on GGO detectability has been of long‐standing interest in the investigation of LDCT performance. However, most previous reports on the technical aspects of LDCT have only studied the effects of dose level and/or image noise (i.e., standard deviation) 14 , 15 , 16 . To our knowledge, only a single published report has described the results of modulation transfer function (MTF) as a resolution property index (9) .…”
Section: Introductionmentioning
confidence: 99%